Seeds of yesterday - Andrews, V. C. (Virginia C.) (New York : Pocket Books, 1984)
Living in a rebuilt Foxworth Hall as man and wife, Chris and his sister Cathy believe they have at last found happiness, only to watch helplessly--horribly--as history repeats itself.
Fifth book about the Dollanganger family.
Keywords: Mothers and daughters -- Juvenile fiction; Problem families -- Juvenile fiction; Revenge -- Juvenile fiction; Horros fiction